Vaginal Laceration in an Open Pelvic Fracture Case Report: A Novel, Prophylactic Antibiotic Delivery Mechanism - Nishant Suneja; Eric H. Tischler; Skye Lockwood; Adam J. Wolfert; Daniel Martingano; Piyapa Praditpan; Thomas Lyon (Case Reports in Orthopedics)
Introduction. Rotational displaced pelvic ring injuries are associated with internal injuries to both the gastrointestinal and genitourinary viscera and anatomic structures. Vaginal lacerations and open genitourinary-associated injuries are at increased risk of mortality due to sepsis. Case Presentation. This case presents a 65-year-old female status post-pedestrian-vehicle struck diagnosed with an open pelvic fracture with extension into the outer one-third of the vaginal wall. The patient was successfully treated with emergent surgical debridement, pelvic stabilization, and internal placement of a novel combination of metronidazole antibiotic gel and vancomycin/tobramycin Polymethyl methacrylate beads. Conclusion. No evidence of infection was observed with the use of topical metronidazole-coated vancomycin/tobramycin Polymethyl methacrylate beads for contaminated open pelvic fracture injury involving the vaginal wall. Further research on antibiotic gels for use in high-risk open fractures is required.